Effects of surface geology and topography on the damage severity during the 2015 Nepal Gorkha earthquake - K. Sharma; M. Subedi; R.R. Parajuli; B. Pokharel (International Association of Lowland Technology, 2017)
An earthquake of moment magnitude (Mw) 7.8 struck Nepal at 06:11 UTC on April 25, 2015. A field reconnaissance was carried out immediately after the main shock. This paper presents the accelerograms and the geology of Nepal. The acceleration response spectra of the motions at the valley show a prominent amplification at the period of 5 sec. This paper describes the effects of local geology and topography on the damage severity during the earthquake. The damage patterns illustrate the strong influence of local geology conditions on the severity of the damage at many places, like soil amplification in Gongabu, Machhapokhari, Ramkot, Purano Naikap, areas along the major rivers in Kathmandu Valley with loose alluvium deposits, and ridge effects on the Swayambhu Nath hill and Chautara. The effect of low frequency amplification caused by the Kathmandu Valley basin is evident from the severe damage to well-designed tall buildings in Kathmandu. Severe damages including ground fissures and liquefactions were observed adjacent to basin edges around the Kathmandu Valley. It was concluded on the basis of the observation that local geology, rather than engineering features of structures, largely determined the severity of damage during the earthquake.